2003
DOI: 10.1152/physiolgenomics.00076.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of reduced β-adrenergic signaling in the aged heart as revealed by genomic profiling

Abstract: .-Myocardial aging leads to a reduction of ␤-adrenergic receptor-induced metabolic and contractile responsiveness. We hypothesize that a change in the patterns of gene expression is important in these age-related events. To test this, hearts were harvested from young and aged male rats (3-4 and 20-22 mo, respectively). Total mRNA was extracted and prepared for hybridization to Affymetrix U34A GeneChips. Filtering criteria, involving fold change and a statistical significance cutoff were employed, yielding 263 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
5
15
0
Order By: Relevance
“…Several studies support impaired adenosine responses in aged heart [59][60][61][62]64,[71][72][73], though findings regarding AR expression/signaling vary [16,60,71]. Our recent data verifies failure in adenosinergic protection with even moderate aging in mouse [16], consistent with findings of Gao et al [64] and Schulman et al [65] in aged rat hearts.…”
Section: Age-related Failure Of Intrinsic Cardioprotection-the Adenossupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies support impaired adenosine responses in aged heart [59][60][61][62]64,[71][72][73], though findings regarding AR expression/signaling vary [16,60,71]. Our recent data verifies failure in adenosinergic protection with even moderate aging in mouse [16], consistent with findings of Gao et al [64] and Schulman et al [65] in aged rat hearts.…”
Section: Age-related Failure Of Intrinsic Cardioprotection-the Adenossupporting
confidence: 88%
“…Despite no change in baseline A 1 AR expression in rat [60] and mouse [16], age-related changes in Adora1 mRNA are observed, though findings vary. Arosio et al [88] and Dobson et al [73] observed elevations in Adora1 whereas Jenner et al [89] reported a 5-fold reduction in Adora1 with age. Irrespective of effects of age on mRNA, it appears that changes do not translate into altered A 1 AR expression [16,60].…”
Section: Intrinsic Cardioprotection Via Adenosine Receptors: Effects mentioning
confidence: 98%
“…β 2 -AR desensitization related GRK activity and expression of GRK2, GRK3, but not GRK5 and β-arrestin, increase as an organism ages (Schutzer et al, 2001). In addition, the gene expression profiles for aged myocardial tissues showed a reduction in β 2 -AR-induced metabolic and contractile responsiveness, and an increase in β-arrestin mRNA expression (Dobson et al, 2003). Our results also show that GRK3 and β-arrestin desensitization systems are associated with decreased epinephrine-induced gluconeogenesis.…”
Section: Discussionsupporting
confidence: 53%
“…Electric shock induced catecholamine secretion from the adrenal medulla together with decreased blood glucose responses in old rats (Mabry et al, 1995). Catecholamine-stimulated lipolysis, glycogenolysis, and β 2 -AR mediated vasorelaxation all declined in aged animal aortic tissues (Dax et al, 1981;Fraeyman and van Ermen, 1993;Dobson et al, 2003). To understand the reasons for the reduced response to β 2 -AR-stimulated intracellular function, aged rat hepatocyte viability, receptor density, receptor binding affinity, and adenylate cyclase activities were studied (Morgan et al, 1983;Fraeyman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Snyder et al (44) identified a decrease in the release of norepinephrine, which may affect blood pressure and %FS. Indeed, others also have shown a reduced response to catecholamines in aged aortas and hearts (5,19,25,38,44). Arosio et al (5) also have reported an increase in adenosine A 1 receptor gene expression in the aging rat heart, which would have a similar antiadrenergic effect.…”
Section: Discussionmentioning
confidence: 98%